The stability studies and in vitro hepatic microsomal metabolism of some alpha-phenyl-N-substituted nitrones in rats - (:unkn) unknown (SPRINGER FRANCE, 2004)
Nitrones are a very important class of synthetic chemicals as synthetic intermediates, antioxidant agents, and metabolic oxidation products of secondary amines and imines used drug, food, cosmetic and printing industry. In the present study, the stability experiments and in vitro metabolism studies using rat microsomal preparations fortified with NADPH were carried out using three different alpha-phenyl-N-substituted nitrones ie alpha-phenyl-N-tert-butylnitrone (PTBN), alpha-(2,6-dichlorophenyl)-N-phenylnitrone (DCPPN) and alpha-phenyl-N-adamantanylnitrone (PADN). The separation of these compounds from the potential degradation, isomerization and metabolic products were performed using a reverse phase HPLC system with a diodearray uv detection. Following stability experiments at 37degreesC using methanolic nitrone solutions, it was observed that PTBN produced trace amounts of benzaldehyde and the corresponding amide. DCPPN also produced trace amounts of amide. After 12 hours, the amount of the amide significantly increased. PADN produced trace amount of benzaldehyde but not any amide. The proposed compounds were incubated with rat microsomal preparations fortified with NADPH, extracted into dichloromethane (DCM) and finally evaporated under nitrogen in the dark conditions. PTBN was metabolized into corresponding amide whereas DCPPN and PADN did not. With all of the substrates, the corresponding aldehydes are observed with both test and control tubes using denaturated microsomes and without co-factors.
Keywords: nitrones; nitrone metabolism; amides; AMIDES